Case report: Stem cell-based suicide gene therapy mediated by the herpes simplex virus thymidine kinase gene reduces tumor progression in multifocal glioblastoma - Oraee-Yazdani, Saeed; Akhlaghpasand, Mohammadhosein; Rostami, Fatemeh; Golmohammadi, Maryam; Tavanaei, Roozbeh; Shokri, Gelareh; Hafizi, Maryam; Oraee-Yazdani, Maryam; Zali, Ali-Reza; Soleimani, Masoud (Frontiers in Neurology, 2023)
Introduction: Glioblastoma multiforme (GBM), as a malignant brain tumor, has a poor prognosis despite the current therapies. Suicide gene therapy is a widespread cancer gene therapeutic strategy that requires a prodrug activating gene to encode the activating enzyme which is then transduced into the vector, such as Mesenchymal Stem Cells (MSCs) that injects into the tumor tissue and leads to tumor suppression. Case presentation: A 37-year-old man presented to our center with two evident foci of glioblastoma multiforme at the left frontal and left parietal lobes. The patient received stem cell-mediated herpes simplex virus thymidine kinase (HSV-tk) genes at the frontal focus of the tumor besides ganciclovir as a prodrug for 14 days after injection. For follow-up, the patient was periodically assessed using regular magnetic resonance imaging (MRI). The growth and recurrence pattern of foci were assessed. After the injection on Feb 09, 2019, the patient’s follow-up revealed a recurrence of parietal focus on Dec 19, 2019. However, the frontal focus had a slight and unremarkable enhancement. Until our last radiological follow-up (on Mar 18, 2020) left frontal focus had no prominent recurrence and the size of the left parietal focus increased and extended to the contralateral hemisphere through the corpus callosum. Eventually, the patient passed away on July 16, 2020 (PFS = 293 days, OS = 513 days). Conclusions: The gliomatous focus treated with bone marrow MSC containing the HSV-TK gene, had a different pattern of growth and recurrence compared to a non-treated one.